â€œGENDER EQUALITYâ€ REVISITED: DECONSTRUCTION OF ISLAMIC THOUGHT TOWARDS GENDER EQUALITY - Nurdin Nurdin (STIT Sunan Giri Bima, 2022)
Although the concepts of gender equality in Islam are continuously debated in many Muslim communities due to its patriarchal system in running family life, there are new discourses over gender equality proposed by Muslim scholars to reconstruct old Islamic juristâ€™s views of gender perspective in Muslim family life in which they come up with the concept of equality of gender order in Islam which is in line with the gender perspective in global context that upholds the rights and justices for all gender identity. This research will examine the construction of gender equality in Islamic teaching and its implementation in Bima local culture. This research used a qualitative approach. The techniques of data collection and analysis used literature studies and internet observations. The primary data were grouped from literature review including journal, thesis/dissertation, news related to the issue of gender equality in general and gender order in particular in Bima society. The data were then analyzed descriptively and qualitatively. The research found that gender equality in Islamic perspective upholds the rights for all gender identity both men and women equally, as well as those perspectives have been deeply rooted in Bima local culture in running their family life in everyday life.